Biblioteki wobec pandemii COVID-19. Studium przypadku wybranych profili polskich bibliotek na Instagramie - Pamuła-Cieślak, Natalia (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
This article presents Instagram as a medium used by libraries. The main part of the article is the analysis of the research material - text, visual content, and hashtags posted from September 11, 2019, to September 11, 2020, on five various types of Polish libraries’ Instagram profiles. The analysis of the material from this time period provides answers as to how the Covid-19 pandemic influenced the content published by libraries on Instagram. The analysis takes the form of a case study based on critically examined data collected.